Maxims - Translational Analysis of Theresa May Speeches at the UN General Assembly into Arabic - M. Ali, Dania Abbas (Journal of Innovation in Education and Social Research, 2024)
Basically, euphemisms are words or phrases that talk indirectly about something unpleasant or offensive. This can be shown and explained through the analysis of eupheministic expressions found in political speeches. For now, we are going to explore the Theresa May’s political speeches in order to indicate and highlight the importance of such phenomenon and how to analyze them by using pragmatic means. To put this differently, we can say how euphemistic expressions can hide a great message behind a kind expression or words.